(untitled) (International Journal of Innovative Technologies in Economy, 2023)
This article examines the set of modern tools that ensure regional development: methods, means, forms. It was determined that to ensure the efficiency and effectiveness of the formation and implementation of state policy, it is necessary to use economic, financial, organizational and informational tools. The component of economic regulation is analyzed and its importance for regional development is emphasized. The sequence of stages of implementation of the state regional development policy is considered.